Atopic dermatitis in adolescence - Giampaolo Ricci; Federica Bellini; Arianna Dondi; Annalisa Patrizi; Andrea Pession (PAGEPress Publications, 2011)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder that typically occurs during childhood especially in the first year of life, with a variable frequency from 10% to 30%. Recent studies have shown that in Europe among 10-20% of children with AD suffer from this disorder also in adolescence. AD is a chronic inflammatory skin disease with a typical onset in the first years of life and with a 10- 30% prevalence among young children. AD prevalence in adolescence has been estimated around 5-15% in European countries. AD persists from childhood through adolescence in around 40% of cases and some risk factors have been identified: female sex, sensitization to inhalant and food allergens, allergic asthma and/or rhinoconjunctivitis, the practice of certain jobs. During adolescence, AD mainly appears on the face and neck, often associated with overinfection by Malassezia, and on the palms and soles. AD persistence during adolescence is correlated with psychological diseases such as anxiety; moreover, adolescents affected by AD might have problems in the relationship with their peers. Stress and the psychological problems represent a serious burden for adolescents with AD and cause a significant worsening of the patients' quality of life (QoL). The pharmacological treatment is similar to other age groups. Educational and psychological approaches should be considered in the most severe cases.